Relationships between food choices, physical activity, glycated haemoglobin and Body Mass Index in type 1 diabetes patients treated with personal insulin pumps - what else can surprise? - Krzyżowska, Sabina; Cyranka, Katarzyna; Matejko, Bartłomiej; Witek, Przemysław; Cyganek, Katarzyna; Kieć-Wilk, Beata; Klupa, Tomasz (Progress in Nutrition, 2023)
Background and aim: The aim of the study was to find the relationship between food choices and physical activity, glycated haemoglobin and body mass index among people with type 1 diabetes without complications treated with personal insulin pumps. Methods: A cross-sectional study was conducted using a Beliefs and Eating Habits Questionnaire with additional follow-up questions. The data from the questionnaire and the last glycated haemoglobin from the patient file were used. Results: We included 116 patients with type 1 diabetes and founded the relationship between physical activity at leisure and snacking in the subgroup of men (p=0.009). Overweight was more common among men. It has been shown that people with glycated haemoglobin over 7% (53 mmol/mol) preferred light products (p=0.003). In the univariate logistic regression model the choice of light products was influenced by gender, age, glycated haemoglobin level and physical activity at leisure. The statistically significant relationship was found between the physical activity at leisure and the frequency of white bread and rolls (p=0.016). Conclusions: We found that men with low and moderate physical activity snack more between meals. Light products were significantly associated with higher level of glycated haemoglobin and weight. Despite good glycaemic control, patients should be reminded and educated about proper nutrition and the selection of good products during physical activity at work and at leisure, taking into account the parameter such as Body Mass Index.